Two-hour hyperoxia following experimental neonatal asphyxia produces morphological brain damage - Benavides, Melva (2013)
Objectives: To determine the effect of 2-hour exposure to 21% O2, 40% O2 and 100% O2 on cerebral morphology in an experimentalmodel of neonatal asphyxia. Design: Experimental study. Setting: Instituto Nacional de Salud del Niño, Lima, Peru. Biologic material:Holtzman albino rats. Interventions: A sample of 120 one week-old Holtzman albino rats (with the exception of the control group)underwent experimental asphyxia by left carotid artery ligation and then exposition to hypoxia (8% O2); thereafter rats were randomlyassigned to one of the following groups: exposition for two hours to 100% O2, to 40% O2, to 21% O2, and a control group (notexposed to experimental asphyxia). Brain damage was determined by brain weight and percentage of microscopic brain area damage.Main outcome measures: Brain damage. Results: Brain weight was lower in animals with experimental hyperoxia (ANOVA, p<0.001).Microscopic damage was more frequent in the group receiving 100% O2 for two hours and with less frequency in the group receiving40% O2 (60% versus 43.3%). The difference was statistically significant (χ2 test: p<0.001). The group receiving 100% O2 had moremicroscopic brain damage (18.3 %) in comparison with the other groups of experimental hypoxia, but the difference was not statisticallysignificant (ANOVA, p=0.123). Conclusions: Following neonatal asphyxia 100% two-hour hyperoxia was associated with less brainweight and more damage in experimental animals.